Patterns of splenic arterial enhancement on computed tomography are related to changes in portal venous pressure. Issue 3 (March 2019) - McCormick, P. Aiden; Malone, Dermot E.; Docherty, James R.; Kiat, Clifford; Christopher, Brian T.; Chin, Jun Liong
Abstract : Objectives: One of the striking features of splenic imaging is variable heterogeneous gyriform arterial enhancement on dynamic computed tomography (CT). We speculated that these patterns of arterial enhancement may reflect changes in splenic micro-circulation related to changes in portal venous pressure. Patients and methods: To test this hypothesis, we evaluated arterial phase CT scans performed before and after liver transplantation ( n =91), as this is the most effective way of alleviating portal hypertension. We developed novel grading systems to assess heterogeneity. Two control groups were used: patients with cirrhosis undergoing transarterial chemoembolization (TACE) ( n =28) and patients with cirrhosis on the liver transplant waiting list who had repeated CT scans ( n =28). Results: Splenic arterial heterogeneity increased in 55% of transplant patients compared with 14% in the TACE patients and 4% in the waiting list patients ( P <0.0001). Mean Hounsfield units in areas of splenic enhancement were 71.7±2 before transplant and 90.1±2.5 after transplant ( P <0.01). In contrast, there were no significant changes following TACE (86.3±4.2 vs. 83.5±4.5; P =NS) or in waiting list patients (80.9±4.6 vs. 73.8±3.7; P =NS). Conclusion: We have shown the heterogeneous gyriform enhancement patterns significantly increase following liver transplantation but not after TACE or in waiting list patients. We suggest that these changes are due to the reduction in portal venous pressure and likely reflect changes in splenic micro-circulation. These changes may be important in the pathophysiology of hypersplenism.